Ring‐opening of Epoxides Mediated by Frustrated Lewis Pairs. Issue 48 (23rd July 2018) - Krachko, Tetiana; Nicolas, Emmanuel; Ehlers, Andreas W.; Nieger, Martin; Slootweg, J. Chris
Abstract: Treatment of the preorganized frustrated Lewis pairs (FLPs) t Bu2 PCH2 BPh2 (1 ) and o ‐Ph2 P(C6 H4 )BCat (Cat=catechol) (4 ) with 2‐methyloxirane, 2‐phenyloxirane and 2‐(trifluoromethyl)oxirane resulted in epoxide ring‐opening to yield the six‐ and seven‐membered heterocycles2 a –c and5 a –c, respectively. These zwitterionic products were characterized spectroscopically, and compounds2 a, 2 b, 5 a and5 c were structurally characterized by single‐crystal X‐ray structure analyses. Based on computational and kinetic studies, the mechanism of these reactions was found to proceed via activation of the epoxide by the Lewis acidic borane moiety followed by nucleophilic attack of the phosphine of a second FLP molecule. The resulting chain‐like intermediates afford the final cyclic products by ring‐closure and concurrent release of the second equivalent of FLP that behaves as catalyst in this reaction. Abstract : The stoichiometric reactions of methylene‐ (right) and o ‐phenylene‐bridged (left) P/B‐based frustrated Lewis pairs with mono‐substituted epoxides result in epoxide ring‐opening and the formation of six‐ and seven‐membered heterocycles, respectively. In addition, insights into the reaction mechanism are provided based on DFT calculations as well as kinetic analyses.